Fine needle aspiration of abdominal organs: a review of current recommendations for achieving a diagnostic sample. (26th July 2017) - Liffman, R.; Courtman, N.
Abstract : With the improved accessibility to ultrasound, fine needle aspiration of abdominal organs is now performed frequently in many veterinary practices. Despite this, there are many 'unknowns' as to the best method to produce a high‐quality sample. This report begins by highlighting recent literature on the risks and benefits of abdominal fine needle aspiration. It follows with recommendations about the equipment and method best suited to the procedure, including needle and syringe size and aspiration versus non‐aspiration techniques. Various smear preparations and laboratory submission requirements are also discussed. The final aspect of the review more specifically discusses fine needle aspiration of specific abdominal organs: the liver, kidney, spleen, pancreas, urinary bladder, prostate and abdominal lymph nodes.